Building Students' Emotional Quotient Through Religion Teaching in Public Higher Institution - K, Munawir (Islamic Studies and Development Center (ISDC) Universitas Negeri Padang, 2019)
This research is aimed to identify whether religion teaching in Public Higher Institution is able to shape students’ emotional quotient. This research used quantitative method with survey approach, the entire data were collected through documentary analysis to four hundred students who are selected from fifteen majors and they have accomplished religion teaching course on the semester August to December 2018. All data were analyzed descriptively using thematic techniques. Relatively the results of this research show that religion teaching course in Public Higher Institution is able to shape students’ emotional quotient, that fact affects the students in nine aspects; i) positive thinking, ii) patience, iii) honesty, iv) confidence, v) consistency, vi) responsibility, vii) discipline, viii) intention and ix) hard working. By referring to the results, it can be seen clearly that Islamic religion teaching course has a significant role in implementing national education vision to shape an intelligent human intellectually and emotionally.